HUBUNGAN PENGGUNAAN GADGET DENGAN KESEHATAN MENTAL PADA SISWA SMP NEGERI 4 PASSI TAHUN 2024 - Kristina Pesak; Mesak Rambitan; Alva Supit (Yayasan Syalom Cipta Sumikolah, 2024)
Indonesia ranks as one of the countries where people spend the most time per day using gadgets, with each individual averaging around 6.05 hours daily on cellphones or similar devices. The majority of this time is spent accessing the internet, playing games, watching videos, sending messages, and making phone calls. However, excessive gadget use can have negative impacts on the mental and physical health of users, especially school children. This research aims to determine the relationship between gadget use and mental health among students at SMP Negeri 4 Passi. A cross-sectional design was used, tested quantitatively. The population consisted of all students at SMP Negeri 4 Passi (total sampling, n=55). Gadget use and mental health were assessed using a questionnaire and rated on an ordinal scale (bad, moderate, good). The relationship between these two variables was analyzed using the chi-square test, with a significance level of p < 0.05 indicating a relationship. Analysis of the 55 respondents showed that 40% were male, 43.6% were 13 years old, and 40% were from grade IX. Statistical testing yielded a p- value of 0.010, leading to the conclusion that there is a significant relationship between gadget use and mental health.